Hedgehog regulates smoothened activity by inducing a conformational switch. - Zhao, Y.; Tong, C.; Jiang, J. (Nature, 2007)
Hedgehog (HH) morphogen is essential for metazoan development. The seven-transmembrane protein smoothened (SMO) transduces the HH signal across the plasma membrane, but how SMO is activated remains poorly understood. In Drosophila melanogaster, HH induces phosphorylation at multiple Ser/Thr residues in the SMO carboxy-terminal cytoplasmic tail, leading to its cell surface accumulation and activation. Here we provide evidence that phosphorylation activates SMO by inducing a conformational switch. This occurs by antagonizing multiple Arg clusters in the SMO cytoplasmic tail. The Arg clusters inhibit SMO by blocking its cell surface expression and keeping it in an inactive conformation that is maintained by intramolecular electrostatic interactions. HH-induced phosphorylation disrupts the interaction, and induces a conformational switch and dimerization of SMO cytoplasmic tails, which is essential for pathway activation. Increasing the number of mutations in the Arg clusters progressively activates SMO. Hence, by employing multiple Arg clusters as inhibitory elements counteracted by differential phosphorylation, SMO acts as a rheostat to translate graded HH signals into distinct responses.